Sustainable management of black soils: from practices to policies - Fontana, Ademir; Klimanov, Anatoly; Loss, Arcangelo; Clerici, Carlos; Wei, Fan; Qu, Jianhua; Carfagno, Patricia; Baron, Vern; Liu, Xiaoyu; Chen, Xueli; Labaz, Beata (FAO, 2022)
In the coming decades, a crucial challenge for humanity will be meeting future food demands without further undermining the integrity of the Earth’s environmental systems. As the food basket of the world, black soils are already degraded significantly after land use change from natural ecosystem to farmland, but main soil threats such as erosion by water and wind, loss of soil organic carbon (SOC) and soil organic matter (SOM), and nutrient imbalance will further endanger its ecosystem service functions. For example, during the past several decades, black soils have lost about 50 percent of their initial SOC stock due to soil erosion, degradation, and other unsustainable human activities (Gollany et al., 2011). Responding to these threats, there is increasing focus on ‘Sustainable Soil Management’ as a means to maintain or increase productivity on underperforming black soils while simultaneously decreasing the environmental impacts of management practices. However, it is unclear what such efforts might entail for the future of intergraded management practices and policy strategies for black soil conservation. Here we present a global scale assessment of sustainable management practices of black soils that may be necessary to achieve increased yields and decreased environmental impact.